Genetic aspects of reproduction. - Fuchs, Fritz (2015)
The fields of genetics and reproduction are as inseparable as Siamese twins, although geneticists and reproductive biologists move in different circles and rarely ever read about the work of others. Genetics is the science that deals with the transfer of the characteristics of the species from generation to generation and Reproductive Biology is the science related to all the necessary mechanisms to create a generation to the next.